2010
DOI: 10.1007/s00384-010-0901-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the chemokines GRO-2, GRO-3, and interleukin-8 in colon cancer and their impact on metastatic disease and survival

Abstract: In accordance with earlier findings, we report here a significantly increased expression of GRO-2, GRO-3, and IL-8 in colon carcinoma as compared to normal tissue. Furthermore, GRO-3 was related to metastasis formation, and IL-8 was associated with survival, suggesting a potential predictive power of these markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 37 publications
11
89
1
1
Order By: Relevance
“…CXCL2 relative expression has been found to be low in breast cancer (19) and elevated in an estrogen receptor-positive breast cancer type in another study (20). The same levels of expression have been found in normal and adenocarcinoma samples of the colon (21), while it was significantly elevated in colon cancer compared with normal adjacent tissue, facilitating cancer cell invasion and metastasis, and correlated with an unfavorable outcome in other studies (22,23). However, little is known about the expression of CXCL2 in HCC and its correlation with the clinical disease outcome.…”
Section: Introductionmentioning
confidence: 54%
“…CXCL2 relative expression has been found to be low in breast cancer (19) and elevated in an estrogen receptor-positive breast cancer type in another study (20). The same levels of expression have been found in normal and adenocarcinoma samples of the colon (21), while it was significantly elevated in colon cancer compared with normal adjacent tissue, facilitating cancer cell invasion and metastasis, and correlated with an unfavorable outcome in other studies (22,23). However, little is known about the expression of CXCL2 in HCC and its correlation with the clinical disease outcome.…”
Section: Introductionmentioning
confidence: 54%
“…[13][14][15][16][17] They also have been reported to be involved in angiogenesis 27 and metastasis. 28,29 Notably, Table 1. GeXP hInflamPlex data normalized to GAPDH (A), real-time PCR data normalized to GAPDH (B), GeXP hInflamPlex data normalized to B2M (C), and real-time PCR data normalized to B2M (D).…”
Section: Org)mentioning
confidence: 99%
“…CXCL8 and the two CXCL8 receptors are expressed in prostate cancer tissues (Murphy et al 2005). Furthermore, among the ELR-CXC chemokines, CXCL1-3 [growth-related oncogene (GRO)-α, -β, and -γ] are highly expressed in colon cancer cells (Doll et al 2010) and also in tumor-infiltrating neutrophils, tumor-associated macrophages, and endothelial cells, suggesting that multiple ELR-CXC chemokines can regulate the tumor microenvironment (Brat et al 2005;Charalambous et al 2005). Clinical studies have confirmed the increased expression of CXCL8 in the more advanced stages of cancers, which indicates that suppression of ELR-CXC chemokine activity may be an important therapeutic approach for aggressive and metastatic tumors .…”
mentioning
confidence: 99%